2014
DOI: 10.1016/j.ejpb.2014.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Positive-charged solid lipid nanoparticles as paclitaxel drug delivery system in glioblastoma treatment

Abstract: You may download, copy and otherwise use the AAM for non-commercial purposes provided that your license is limited by the following restrictions: (1) You may use this AAM for non-commercial purposes only under the terms of the CC-BY-NC-ND license. (2) The integrity of the work and identification of the author, copyright owner, and publisher must be preserved in any copy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…This drug is currently used for the treatment of breast, ovarian, lung, and colon cancers 16 . More recently different strategies based on liposomes or nanoparticles with Paclitaxel have also been investigated in glioma [58][59][60][61] . Based on this knowledge, this work aimed to investigate the possibility to trigger macrophage mediated tumor cytotoxicity based on a TLR4 activation using Paclitaxel drug as ligand.…”
Section: Discussionmentioning
confidence: 99%
“…This drug is currently used for the treatment of breast, ovarian, lung, and colon cancers 16 . More recently different strategies based on liposomes or nanoparticles with Paclitaxel have also been investigated in glioma [58][59][60][61] . Based on this knowledge, this work aimed to investigate the possibility to trigger macrophage mediated tumor cytotoxicity based on a TLR4 activation using Paclitaxel drug as ligand.…”
Section: Discussionmentioning
confidence: 99%
“…PTX and mainly DOX effects on cell viability were more irreversible, suggesting that, once the way to overcome the BBB is found, these drugs can be effective cytotoxic agents against glioma cells. For this purpose, we are studying new nanoparticle systems able to efficiently vehiculate hydrophilic compounds across the BBB to the site of tumor [118,119]. …”
Section: In Vitro Cytotoxicity Study On Neurospheres (Ns) and Adhementioning
confidence: 99%
“…In vitro biological tests (MTT assay and uptake by confocal laser scanning microscopy (CLSM)) highlighted a greater effectiveness in reducing the cancer cells viability for DDAB-coated-NLC, probably related to their greater cellular uptake, observed with a great amount of green fluorescent NLC both in the cytosol and in the nucleus of U87MG cells. Contrary to the behavior of DDAB, other positive-charged materials such as stearylamine (SA) and glyceryl chitosan (GC) were found to not significantly affect the brain uptake of paclitaxel (PTX)-loaded SLN prepared with the fatty acid coacervation technique [41]. Interestingly, in vitro studies performed on glioblastoma cells (U87MG) in co-culture with a cells monolayer of hCMEC/D3, assumed as an in vitro model of BBB, showed that PTX efficacy against glioblastoma cells increased when PTX was loaded into the SLN, without any significant difference between the uncharged and the positively charged SLN.…”
Section: In Vitro Proof-of-conceptmentioning
confidence: 81%
“…Interestingly, in vitro studies performed on glioblastoma cells (U87MG) in co-culture with a cells monolayer of hCMEC/D3, assumed as an in vitro model of BBB, showed that PTX efficacy against glioblastoma cells increased when PTX was loaded into the SLN, without any significant difference between the uncharged and the positively charged SLN. The increased efficacy of PTX-loaded SLN compared to the free drug could be probably due to an improved permeation through the endothelial cell monolayer related to the carrier ability to overcome the efflux by P-glycoprotein [41]. Recently, SLN prepared by fatty acid coacervation technique and containing behenic acid as lipid matrix, were studied for the delivery of doxorubicin (DOX) [42].…”
Section: In Vitro Proof-of-conceptmentioning
confidence: 99%